A EDUKASI TERAPI PENGOBATAN HIPERTENSI PADA MASYARAKAT DI DESA BOTOMULYO KECAMATAN CEPIRING KENDAL: EDUKASI TERAPI PENGOBATAN HIPERTENSI PADA MASYARAKAT DI DESA BOTOMULYO KECAMATAN CEPIRING KENDAL - rosa, elvira; Haini Santi; Megananda; Arlina Safitri; Nur Lazimah (JURNAL ABDIMAS DOSMA (JAD), 2022)
Hypertension is one of the main causes of mortality and morbidity in Indonesia, so the management of this disease is a very common intervention carried out at various levels of health facilities. This clinical practice guide was prepared to facilitate health workers in Indonesia in dealing with hypertension, especially those related to heart and blood vessel disorders. Symptoms of hypertension include headache, restlessness, blurred vision, chest pain, heart palpitations, dizziness and fatigue. There are several risk factors that can cause hypertension, including genetics, obesity, gender, stress, lack of exercise, salt intake and diet patterns, and smoking habits. The purpose of this community service activity is for Plamongan Sari IV residents to be able to know the symptoms, prevention, risk factors, use of drugs and types of hypertension drugs. The result of this activity is that community service activities run smoothly and residents are very enthusiastic about these activities. Residents are very happy to be given assistance and education on hypertension treatment therapy and receive free basic necessities and toga plants.